Lexical Characteristics of Absolution of Sins in the Klimantović’s Miscellany from 1512 - Lozić Knezović, Katarina (Poznańskie Studia Slawistyczne, 2013)
This paper presents the lexical and linguistic characteristics of absolution of sins in the Croatian Church Slavonic Klimantović’s Miscellany I, in which the patterns of release and absolution from sin are powerful oral mechanism adjusted to population of that time. In the analysis, the author used her own transliteration of the miscellany. Considered are the sacraments of reconciliation in chapters 32. Otrišenie op’ĉeno, 36. Ovo ẽod’rišenie od’rišiti od’ velikoga prok’lats’tvaand 37. Ovo estьod’rišenie od’rišiti nemoĉnika muž’ku i žen’sku gl vu. The study shows how much the language is considered archaic in those chapters as well as how much there are younger lexical influences, conditioned primarily by neighborly contacts that influenced vernacular. Archaic features of the vocabulary are recorded in domestic words from Protoslavic period as well as from dialectal Protoslavic layers, with a significant number of Moravisms (West Slavic lexemes) such as zakonь, suffix -kratь, adjective nebes’ki, verb otpustiti. Contribution to that are loanwords from Protoslavic period. Among other linguistic features, confirmations of archaic features are the older verb present tense forms -ši. The rejuvenation of lexis is obvious in the influence of vernacular on texts of absolution – in many Italianisms that entered into our system directly through Čakavian dialect such as eneralь, pun’ta, purgatorii, and in numerous Croatisms as a result of direct influence of vernacular which is not part of a joint Church Slavonic and Croatian lexis such as personal pronoun ĵa, the dative singular mani, interrogative pronoun čakoli, connective ako. Also, among other linguistic features are present for example younger suffixes -ega, -oga of the genitive singular of adjectives and pronouns.